1980
DOI: 10.1007/bf02408540
|View full text |Cite
|
Sign up to set email alerts
|

Human vertebral bone: Relation of strength, porosity, and mineralization to fluoride content

Abstract: Radiographically normal vertebral bone cylinders from 80 male subjects were tested mechanicallly by static compression and analyzed for porosity, fluoride and ash content. As a group, they had low fluoride content, suggesting little prior intake, consonent with this geographic area. Nevertheless, increasing levels of fluoride were associated with bulkier bone, less porosity, and less mineral per unit of bone, which in direction though not degree suggested changes similar to those of osteomalacia and opposite f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 26 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…We have demonstrated that after 10 days of treatment with a daily oral dose of 40 µmol/100 g of body weight, bone mass of rats increases significantly [8]. The same results were obtained by others, but the quality of bone formed under fluoride administration is still matter of study [9]. Apart from the mentioned effects on bone, fluoride has effects on the secretion of insulin and in the homeostasis of glucose, both when administered as a single dose or in chronically treated rats [8,10].…”
Section: Introductionsupporting
confidence: 79%
“…We have demonstrated that after 10 days of treatment with a daily oral dose of 40 µmol/100 g of body weight, bone mass of rats increases significantly [8]. The same results were obtained by others, but the quality of bone formed under fluoride administration is still matter of study [9]. Apart from the mentioned effects on bone, fluoride has effects on the secretion of insulin and in the homeostasis of glucose, both when administered as a single dose or in chronically treated rats [8,10].…”
Section: Introductionsupporting
confidence: 79%